Perilaku Komunikasi Ibu-Anak pada Anak Usia Dini yang Mengalami Temper Tantrum - Tarissa Madina; Uud Wahyudin; Yuliani Dewi Risanti (Universitas Katolik Widya Karya Malang, 2023)
The phenomenon of temper tantrums indicates an indication of inhibited emotional development in children which makes children express the negative emotions they feel through aggressive behavior. Therefore, good communication behavior is needed from parents, especially mothers as the closest scope owned by children to deal with the condition of children who experience tantrums. This study aims to determine the motives, experiences, and behavior of mother-child communication in dealing with children who experience temper tantrums, as well as to know the meaning of the phenomenon of temper tantrums for mothers. This study uses a qualitative method with a phenomenological study approach and in collecting data using interview techniques. The main informants in this study were five mothers who had experience in handling their children who experienced temper tantrums at an early age. The results showed that the because of motives were due to the mother's communication behavior in dealing with children who experienced temper tantrums at an early age, including mothers having sensitivity and awareness towards children who experienced speech delay. The existence of several conditions that could trigger tantrum behavior in children to appear, such as events that occurred or experienced by the child is not in accordance with his expectations. In addition, through the communication behavior that is carried out, the mother has hope as an in order to motive so that in the future the child can communicate well. There are several communication behaviors that are carried out by mothers in dealing with the aggressive behavior of children they receive, such as inviting communication and giving understanding, providing opportunities and space for children, giving physical touch, not leaving children alone, scolding, and cutting off children's behavior, tweaking, and applying patterns. routine communication with children every day. Meanwhile, mothers interpret the phenomenon of temper tantrums that occur in children as something that makes them sad, tired, stressed, and embarrassed. However, mothers think this is also a test and part of the child's development process that they have to face and go through.